1998
DOI: 10.1037/1040-3590.10.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating attention deficit hyperactivity disorder using multiple informants: The incremental utility of combining teacher with parent reports.

Abstract: In a sample of students referred to a school-based Pupil Assistance Committee, the Inattention and Hyperactivity-Impulsivity factors of the Attention Deficit Hyperactivity Disorder (ADHD) Rating Scale-IV were used to predict diagnostic status, determined by a parent-reported diagnostic interview and teacher rating scale. Results of logistic regression and receiver operating curve analyses indicated that the Inattention and Hyperactivity-Impulsivity factors differentiated students with ADHD from controls and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
1
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 32 publications
(59 reference statements)
4
79
1
5
Order By: Relevance
“…Riccio, Hynd, Cohen, and Gonzalez (1993) found that teacher ratings of ADHD and other behavioural problems predicted performance on a measure of set-shifting, whereas parent ratings failed to do so. Together with these earlier studies, the present study fits with the finding that teachers, as opposed to children and parents, are the optimal informants for ADHD symptoms (Loeber, Green, & Lahey, 1990;Loeber, Green, Lahey, & Stouthamer-Loeber, 1989, 1991Power et al, 1998).…”
Section: Speed Of Inhibition Predicts Teacher-rated Medication Responsupporting
confidence: 90%
“…Riccio, Hynd, Cohen, and Gonzalez (1993) found that teacher ratings of ADHD and other behavioural problems predicted performance on a measure of set-shifting, whereas parent ratings failed to do so. Together with these earlier studies, the present study fits with the finding that teachers, as opposed to children and parents, are the optimal informants for ADHD symptoms (Loeber, Green, & Lahey, 1990;Loeber, Green, Lahey, & Stouthamer-Loeber, 1989, 1991Power et al, 1998).…”
Section: Speed Of Inhibition Predicts Teacher-rated Medication Responsupporting
confidence: 90%
“…Assim sendo, tanto a aprendizagem quanto a socialização de escolares desatentos revelam prejuízos capazes de se configurarem como reais problemas na vida acadêmica e social (Power, 1998;Bagwell, 2001;Hoza & cols., 2001). Considerando-se que a auto-regulação do comportamento mostra-se deficitária para a criança desatenta, a implementação de atividades empregadas pelo professor, salientando os comportamentos adequados e inadequados e suas conseqüências, provavelmente, possam contribuir para a melhoria dos relacionamentos em sala de aula (Barkley, 1990).…”
Section: Discussionunclassified
“…Na literatura especializada, é possível encontrar a descrição desses problemas, manifestados como dificuldades, distúrbios, síndromes ou transtornos. Atualmente, a referência mais utilizada e de aceitação mundial para a classificação dos problemas de atenção é a da American Psychiatric Association (1994), no Diagnostic and Statistical Manual of Mental Disorders (DSM-IV), que define critérios específicos e rigorosos, permitindo a identificação dos problemas mais graves denominados Transtornos da Falta de Atenção (TDA), que podem ser classificados como tipo predominantemente desatento, predominantemente hiperativo-impulsivo ou tipo combinado (Barabasz & Barabasz, 1996;Biederman & cols.,1997;Gaub & Carlson,1997;Power, 1998;Mitsis & cols., 2000;Tonelotto, 2000).…”
Section: Psicologia Escolar E Educacional 2002 Volume 6 Número 2 141unclassified
See 2 more Smart Citations